DEFINITION OF CAUSES OF DESTRUCTION OF KNIVES FOR THE CHOPPING OF SCRAP METAL ON RS-1200 PRESS SCISSORS IN DROP-HAMMER PLANT OF THE JSC «BELARUSIAN STEEL WORKS – MANAGEMENT COMPANY OF HOLDING «BMС» - I. A. Kovaleva; N. A. Hodosovskaya; A. I. Rozhkov (Литьë и металлургия)
Researches of the reasons of broken knives for the chopping of scrap metal of RS-1200 press scissors are conducted, the reasons of breakage are defined and it is established that premature failure of knives is connected with low values of hardness steel which have been a result of violations of technology of heat treatment at the producer’ plant.